REVITALIZING MURABAHAH FINANCING AGREEMENT IN INDONESIA: A RETURN TO ISLAMIC PRINCIPLES FOR SOCIETAL WELFARE - Dayyan, Muhammad; Abbas, Syahrizal; Furqani, Hafas (Universitas Syiah Kuala, 2024)
The transformation of Murabahah trade agreements into Murabahah financing agreements in banking institutions since the 1970s signifies a significant shift in the Islamic financial landscape. Intended to promote an economy that is just and blessed by Allah SWT, the murabahah financing agreement is a crucial instrument in realizing this goal. However, the evolution of this agreement from a straightforward trading pattern to a credit-based model in Islamic banking has deviated from the original Islamic financing characteristics, rendering it similar to conventional banking practices. This study argues that murabahah financing in Indonesian Islamic banking necessitates three key improvements. Firstly, a unified concept of the murabahah financing agreement should be formulated, consolidating the perspectives of the National Sharia Council of the Indonesian Ulama Council, the Financial Services Authority, Bank Indonesia, and the Indonesian Islamic banking sector. Secondly, the seven Islamic economic principles (tawhid, khalifah, 'adalah, amanah, shura', ta'awun, and ta'aruf) should be actualized in the terms and conditions of murabahah financing agreements between banks and customers. Lastly, the implementation of murabahah financing agreements should be centered on enhancing and developing customers' assets, aligning with the fundamental principles of Islamic finance